Assembly and dynamics of the apple carposphere microbiome during fruit development and storage - Zhimo, V. Yeka; Kumar, Ajay; Biasi, Antonio; Abdelfattah, Ahmed; Sharma, Vijay Kumar; Salim, Shoshana; Feygenberg, Oleg; Bartuv, Rotem; Freilich, Shiri; Whitehead, Susan R.; Wisniewski, Michael; Droby, Samir (Frontiers in Microbiology, 2022)
Microbial communities associated with fruit can contribute to quality and pathogen resistance, but little is known about their assembly and dynamics during fruit development and storage. Three apple cultivars growing under the same environmental conditions were utilized to examine the apple carposphere microbiome composition and structure at different developmental stages and storage. There was a significant effect (Adonis, P ≤ 0.001) of fruit genotype and its developmental stages and storage times on the fruit surface microbial assemblage and a strong temporal microbial community succession was detected (Mantel test: R ≤ 0.5, P = 0.001) in both bacterial and fungal communities. A set of 15 bacterial and 35 fungal core successional taxa and members exhibiting differential abundances at different fruit stages were identified. For the first time, we show the existence of an underlying universal dynamics in the assembly of fruit-associated microbiomes. We also provide evidence of strong microbial cross-domain associations and uncover potential microbe-microbe correlations in the apple carposphere. Together our findings shed light on how the fruit carposphere assemble and change over time, and provide new insights into fruit microbial ecology.